What does spatial alternation tell us about retrosplenial cortex function? - Nelson, Andrew J. D.; Powell, Anna L.; Holmes, Joshua D.; Vann, Seralynne D.; Aggleton, John P. (Frontiers in Behavioral Neuroscience, 2015)
The retrosplenial cortex supports navigation, but there are good reasons to suppose that the retrosplenial cortex has a very different role in spatial memory from that of the hippocampus and anterior thalamic nuclei. For example, retrosplenial lesions appear to have little or no effect on standard tests of spatial alternation. To examine these differences, the current study sought to determine whether the retrosplenial cortex is important for just one spatial cue type (e.g. allocentric, directional or intra-maze cues) or whether the retrosplenial cortex helps the animal switch between competing spatial strategies or competing cue types. Using T-maze alternation, retrosplenial lesion rats were challenged with situations in which the available spatial information between the sample and test phases was changed, so taxing the interaction between different cue types. Clear lesion deficits emerged when intra- and extra-maze cues were placed in conflict (by rotating the maze between the sample and choice phases), or when the animals were tested in the dark in a double-maze. Finally, temporary inactivation of the retrosplenial cortex by muscimol infusions resulted in a striking deficit on standard T-maze alternation, indicating that, over time, other sites may be able to compensate for the loss of the retrosplenial cortex. This pattern of results is consistent with the impoverished use of both allocentric and directional information, exacerbated by an impaired ability to switch between different cue types.